Ecological security assessment of Yunnan Province, China in the context of Production–Living–Ecological space division - Fang Liu; Qian Zhang; Jinliang Wang; Yuexiong Liu; Wanbin Wang; Sen Li (Ecology and Evolution)
Abstract With the rapid development of population, society and economy, human activities have caused serious adverse impacts on the environment, ecosystems and landscape patterns over the long term. In order to address the series of impacts of human activities on the environment, territorial space and resource use, the study of Production–Living–Ecological Space (PLES) and ecological security have all become academic frontiers in the field of sustainable development. In this study, we applied multi‐source data and GIS technology to construct an ecological security evaluation model based on the results of PLES delineation and the Pressure‐State‐Response (PSR) framework, and carried out the three‐period PLES ecological security evaluation for 2000, 2010 and 2020 at the county and grid scales in Yunnan Province. The PLES pattern in Yunnan Province is dominated by ecological space, which accounts for 75%, followed by 23% of production space, with ecological space shrinking from 2000 to 2020. Ecological security in ecological space and living space shows an improving trend from 2000 to 2020. The ecological security of production space improved in 2010 compared to 2000 but then showed a decreasing trend in 2020. Ecological security in ecological space shows that north‐western and southern Yunnan is safer than central Yunnan, while ecological security in living space is safer in central Yunnan, and ecological security in production space is better in southern Yunnan than in northern Yunnan. Comparison with related research results shows that the ecological security evaluation results of PLES in Yunnan Province in this study are scientific and reasonable. The ecological security evaluation model of PLES constructed in this study solves the problem of complex and incomplete ecological security evaluation indexes in the past, and the results of the study are more refined and precise, which provides new ideas for the study of regional ecological security.